Evaluation of the new ICHD-III beta cluster headache criteria. (May 2016) - de Coo, IF; Wilbrink, LA; Haan, J; Ferrari, MD; Terwindt, GM
Aim: In the revised criteria of the International Classification of Headache Disorders (ICHD-III beta) the following items are added to the diagnostic criteria of cluster headache: ipsilateral sensation of fullness in the ear and ipsilateral forehead/facial flushing. We evaluated the possible additional value of these symptoms for diagnosing cluster headache. Methods: In this cross-sectional cohort study of (potential) cluster headache patients we investigated these additional symptoms using a Web-based questionnaire. Patients not fulfilling the ICHD-II criteria for cluster headache but fulfilling the ICHD-III beta criteria were interviewed. Results: Response rate was 916/1138 (80.5%). Of all 573 patients with cluster headache according to ICHD-II criteria, 192 (33.5%) reported ipsilateral ear fullness and 113 (19.7%) facial flushing during attacks. There was no difference in reporting ipsilateral ear fullness and facial flushing between patients who received a diagnosis of cluster headache and patients who did not. None of the patients who did not fulfill all ICHD-II criteria could be categorized as cluster headache according to the ICHD-III beta criteria. Conclusion: The results of this study do not support the addition of ear fullness and facial flushing to the new ICHD-III beta criteria.